CLINICAL SAFETY OF TETRACYCLINE TREATMENT IN NILE TILAPIA (OREOCHROMIS NILOTICUS) - OLIVEIRA, S. L.; COSTA, C. C.; ARACATI, M. F.; RODRIGUES, L. F.; FRANCISCÃO, C. F.; ARAÚJO, K. S.; PULTZ, M. E.; FILLA, M. C.; MONTASSIER, H. J.; BELO, M. A. A. (Ars Veterinaria, 2025)
Antibiotic safety in aquaculture plays a key role in safeguarding animal and human health, reflecting the integrated vision of One Health Policies. This study assessed the clinical safety of orally administered tetracycline, incorporated into feed, in Nile tilapia (Oreochromis niloticus). A total of 128 fish from the same spawning were randomized by weight into 16 tanks (with 100 L of water each, n=8), comprising one control (without treatment with tetracycline) and three treatments receiving 100, 200, or 400 mg/kg body weight of tetracycline (with four tanks per treatment). Fish were sampled on days 4, 8, and 12 of treatment, and on day 16, following a four-day recovery period without tetracycline administration. Hematological, biochemical, and somatic parameters were evaluated. No significant changes were observed in hematocrit, hemoglobin, MCV, MCH, MCHC, creatinine, protein, albumin, cholesterol, triglycerides, or alkaline phosphatase. However, fish treated with 200 and 400 mg/kg showed reduced erythrocyte counts and elevated AST levels, indicating dose-dependent effects. Leukocyte profiles and organ indices remained unaffected. Overall, tetracycline was clinically safe at the tested doses, but caution is warranted for higher doses or extended treatments.